Policy Evaluation in Budget Determination at the Regional Revenue, Financial and Asset Management Agency of Intan Jaya Regency - Trisnanto Trisnanto; Natalia Paranoan; Apriana Toding (Jurnal Impresi Indonesia, 2025)
This study aims to analyze Policy Evaluation in Budget Determination at the Regional Revenue, Financial and Asset Management Agency of Intan Jaya Regency. This study uses a qualitative approach. The object of this research is at the Regional Revenue, Financial and Asset Management Agency of Intan Jaya Regency. Data sources are from primary data and secondary data. Data collection methods: observation, documentation interviews. The informants of this research are 5 employees at the Regional Revenue, Financial and Asset Management Agency of Intan Jaya Regency. Data analysis uses Qualitative descriptive analysis, ranging from Data Reduction, Data Presentation and Conclusion Drawn. This study concludes that: 1) The budget determination process at the Regional Revenue, Financial and Asset Management Agency (BPPKAD) of Intan Jaya Regency, takes place in several stages, starting from policy formulation to the formation of Regional Regulations (Perda) and Regent regulations. The involvement of various parties, including the Regional Revenue and Expenditure Budget (APBD) team and teams from outside the APBD. 2) The budget determination policy at BPPKAD Intan Jaya Regency shows a strong commitment to improve regional financial management through the implementation of performance-based budgeting, stakeholder participation, compliance with regulations, and transparency and continuous evaluation. 3) The implementation of the budget determination policy at BPPKAD Intan Jaya Regency faces significant challenges stemming from limited human resources in the financial sector and the dissatisfaction of some OPDs with the distribution of the budget ceiling. These challenges can hinder the effectiveness of budget management and its impact on regional development.